Billy Pilgrim's Traumatic Symptoms and Triggers in Kurt Vonnegut's Slaughterhouse-Five - Yohanis Mesang; Anik Cahyaning Rahayu (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
Psychological trauma is one of the psychological problems which may happen to a human being. Someone is known to suffer from trauma if he or she shows or experiences some special symptoms. This psychological problem, trauma, can happen due to some triggers or causes. Relating to this problem, this article is about Billy’s psychological trauma in Kurt Vonnegut’s Slaughterhouse-Five. Billy is the main character of the novel who suffers from trauma. His psychological disease can be known from the symptoms he experiences or he shows. Besides the symptoms of trauma experienced by Billy, the triggers or causes of Billy's trauma are also explained in this article, which both of them as the objectives of the research. The analysis uses literary theory of trauma by Cathy Caruth. Because trauma relates to psychology, the psychological approach is used in this research. The method used to analyze Billy’s trauma is descriptive-analytical which means that the data relating to the topic which are taken from the novel are described and analyzed based on the objectives of the research. The findings show that symptoms experienced by Billy are recurrent uncontrollable memories of past traumatic events, losing his enthusiasm for life, delusion about Tralfamadorian planet as well as his adventure in time, and sleep disturbance followed by weeping for no reason. The triggers or causes of Billy’s trauma are the result of his participation in World War II where he witnesses many horrific events like the bombing event in Dresden city and getting humiliation as well as harsh treatment from his fellow soldiers, fellow prisoners, and German soldiers. The other cause is facing the events after the 2nd World War that exacerbates his trauma that is the plane crash he is travelling in and the death of his wife due to carbon monoxide poisoning. In conclusion, after analyzing Billy’s traumatic symptoms and the triggers, it can be stated that Billy really suffers from psychological trauma. All the traumatic events influence Billy’s life, how he sees life, and he responds about life and death.